Chemical analysis of the semipurified extract of Paullinia cupana and evaluation of in vitro inhibitory effects against Helicobacter pylori. Issue 16 (17th August 2020) - Aguiar, Bruna Aparecida Alves; Bueno, Fernanda Giacomini; Panizzon, Gean; Silva, Denise Brentan da; Athaydes, Brena Ramos; Gonçalves, Rita de Cassia Ribeiro; Kitagawa, Rodrigo Rezende; Marques, Leila Larisa Medeiros; Paula, Mariana Nascimento de; Antonelli-Ushirobira, Tânia Mara; Medeiros, Daniela Cristina de; Mello, João Carlos Palazzo de
Abstract: Paullinia cupana Kunth, commonly known as guarana, is a native Brazilian plant species from the Amazon area that presents various biological effects, including antimicrobial action. The aim of this study was to chemically analyse the semipurified aqueous extract (AqF) of the plant and to evaluate the activity of crude (CE), ethyl-acetate (EAF), and AqF extracts against Helicobacter pylori . The chemical profile of AqF was determined based on solid analysis 13 C-NMR, direct infusion mass spectrometry (ESI-MS), and MALDI-TOF. The 13 C-NMR spectrum showed characteristics of flavan-3-ol and oligomeric proanthocyanidins. ESI-MS revealed the presence of procyanidin, caffeic acid and its derivatives. MALDI-TOF analysis detected procyanidins of up to 6 units and profisetinidins of up to 5 units. Whereas CE and EAF showed inhibitory activity against H. pylori, CE, EAF, and AqF presented not high inhibitory activity against urease. The results demonstrate the potential of P. cupana to control and prevent H. pylori infection. Graphical Abstract: